Host suitability for germination differs from that of later stages of development in a rare epiphytic orchid - González Orellana, Normandie
We explore phorophyte suitability for germination and establishment of the epiphytic orchid, Psychilis kraenzlinii. We found that the orchid grows on a subset of the available tree species and shows preference for the endemic Machaonia portoricensis (Rubiaceae). The orchid preferred trees with smoother bark, high water holding capacity and low water retention capacity. Microclimatic conditions under which embryos began pre-germination stages mirrored that of the adult orchid, but germination did not, suggesting that suit-able germination sites are not necessarily the best sites for later stages of development.